THE POLITENESS STRATEGY IN THE FOOD AND BEVERAGE SERVICE SECTION AT LAMPION HOTEL SURAKARTA - SAPUTRO, ARGO LIMPAT KIS; MULIA, VILYA LAKSTIAN CATRA (Politeknik Harapan Bangsa Surakarta, 2020)
Food and Beverage service is a section in the Hotel that is incorporated in Food and Beverage department. To do the responsibility in Food and Beverage Service Section as a Waiter, language is really important in speech acts that will be spoken by waiter. The writer do the research because, the writer want to describe the utterances expressed by the waiter in the Food and Beverage service section in Lampion Hotel Surakarta. The writer is also want to explain the speech acts for reflecting politeness strategy by the waiter in the Food and Beverage section in Lampion Hotel Surakarta. The writer is used qualitative descriptive method in searching the data. The method of finding the data are observing, interviewing, recording, and doing documentation directly on the field. The research shows that Lampion Hotel has utterances expressed and politeness reflection that are conveyed by the waiter there are greeting, offering, asking, repeating, clarifying, inviting and closing that reflected politeness. The writer summarizes that the politeness strategy in the food and beverage service section in the Hotel is very important for those who are working in the hospitality world because it is the main point of the person attitude that will serve the guest with their good personality.